Ibadytskyi tekst pro status akhl al-kabair - Radivilov, Danylo (The Oriental Studies, 2007)

الشيخ صالح بن علي الحارثي (1250هـ/1834م - 1314هـ/1896م) ودوره الاجتماعي والسياسي - الهاشمي, سعيد بن محمد بن سعيد (مجلة دراسات الخليج والجزيرة العربية, 2007)
تهدف هذه الدراسة إلى إلقاء الضوء على سيرة الشيخ صالح بن علي الحارثي ودوره الاجتماعي والسياسي، حيث أدى دوراً بارزاً في أوضاع عمان الداخلية، كما تهدف إلى إبراز مكانة الشيخ العلمية من خلال ثقافته وأثر شيوخه فيه، وتلاميذه الذين تلقوا على يديه العلم، فنشروه في ربوع عمان، خلال النصف الثاني من القرن التاسع عشر؛ حيث حظي بوضع اجتماعي كبير بفضل مواهبه عالماً وزعيماً، وقام برعاية أمور الناس وإصلاح ما بينهم، وعرف بالإمام المحتسب، وتزعم الحزب الهناوي في المنطقة الشرقية وأطاعته القبائل الهناوية في عمان كلها، وعارض حكام عمان وثار عليهم. وعلينا أن نقر قبل أن نلج في هذا الأمر بأن المصادر التي تبحث في حياة هذا الشيخ شحيحة ونادرة للغاية؛ إذ إنها لا تعدو أن تكون مقتطفات متناثرة هنا وهناك غير مترابطة المعالم ولا واضحة الأهداف، مع علمنا بإسهاماته الكبيرة في تشكيل سياسة عمان في عصره، حتى غدت مكانته العلمية والسياسية يعرفها كل فرد، فضلاً عن معاصريه سواء في عمان أو خارجها، وليس مقصودنا بذلك أن الشيخ صالح الحارثي قد رمى بنفسه في أوضاع عمان الاجتماعية والسياسية آنذاك وإنما نقصد أن إرث ذلك العصر قد آل إليه، وبذل هو جهداً مضنياً في محاولته وضع بعض الحلول للمشكلات السياسية في عهده، ولكونه أحد الزعماء الذين بيدهم الحل والعقد من جهة، ولكونه عالماً من جهة أخرى، فلا غرابة أن يطلق عليه لقب ذي الجناحين أو الرئاستين. ويعتمد الباحث في دراسته على مجموعة من المصادر، منها كتاب “تحفة الأعيان“ وكتاب “ الحق الجلي“ لتلميذه نور الدين السالمي، ثم كتاب “نهضة الأعيان“ للشيخ محمد بن نور الدين السالمي، وكتاب “اللؤلؤ الرطب“ للشيخ سعيد بن حمد الحارثي، وكتاب “عين المصالح قي أجوبة الشيخ صالح“ وهو مجموعة من فتاوى الشيخ صالح رتبها سعود بن حميد بن خليفين، وغيرها من المراجع التي تناولت جانباً مهماً من تاريخ عمان في القرن التاسع عشر، مثل كتاب “بدر التمام في سيرة السيد سعيد بن سلطان“ لابن رزيق الذي تناول سيرة السيد سعيد بن سلطان ( 1219 هـ / 1804 م – 1273 هـ / 1856 م )، وغيره من المراجع التاريخية. وبنى الباحث منهجه في تناول سيرة الشيخ صالح ودوره الاجتماعي والسياسي على استقراء ما توافر لديه من معلومات تشير من قريب أو بعيد إلى مكانة الشيخ متتبعاً المصادر التاريخية والفقهية وتحليلها بالقدر الذي يظهر هذه المكانة سلبية كانت أم إيجابية، وسيتضح هذا الأمر في المباحث التالية: 1 - سيرة الشيخ صالح. 2 - تعليمه وثقافته. 3 - دوره الاجتماعي والسياسي.
Keywords: Biographies -- Oman -- 19e siècle

Tethering Stones in Al-Mudhaibi Oman Traps and palaeoclimatic indicators - El-Mahi, Ali Tigani (أدوماتو, 2007)
Keywords: Archéologie -- Oman

جغرافية الموقع و ثقافة المكان : نتائج حفريات موقع بوشر، سلطنة عمان - الجهوري, ناصر سعيد (أدوماتو, 2007)
Keywords: Archéologie -- Oman

Pollen morphology of trees, shrubs and woody herbs of the coastal plain and the monsoon slopes of Dhofar (Sultanate of Oman) - Lippi, Marta Mariotti; Gonnelli, Tiziana; Raffaelli, Mauro (Webbia, 2007)
This paper describes the pollen morphology of the most common trees, shrubs and woody herbs growing in the coastal plain and the escarpment of Dhofar, a wide region in southern Oman. The plant habit and habitat are also reported.
Keywords: Botanique -- Oman

Polygala moggii (Polygalaceae), a new species from Oman - Raffaelli, Mauro; Mosti, Stefano; Tardelli, Marcello (Webbia, 2007)
Polygala moggii grow in a coastal area near Hasik (eastern Dhofar). This new species, apart from its small size and small violet flowers, is also characterized by glabrous unwinged capsules and greenish petaloid sepals without evident nervation. For the characteristics of the sepals, this species resembles some other dwarf species from Somalia and Ethiopia, which have also a limited distribution.
Keywords: Botanique -- Oman

الإباضية: إضافة إلى سلة النتائج - الحديثي, نزار عبد اللطيف (مجلة سبأ, 2007)

الصراع السياسي الديني وأثره في سقوط الإمامة الإباضية الثانية - النابودة, حسن محمد عبدالله (المجلة التاريخية المصرية, 2007)

نشأة الإباضية وأصولهم - الهاشمي, مبارك بن سيف بن سعيد (المجلة العلمية لكلية أصول الدين والدعوة بالزقازيق, 2007)

حيل المعاملات في الفقه الإسلامي - بابكر, خالد بن محمد (دراسات, 2007)

جوانب من التاريخ الاجتماعي والاقتصادي لمدينة تاهرت من خلال كتاب ابن الصغير المالكي - وهرانى, قدور (التراث العربي, 2007)
Keywords: Dynastie rustumide

مقومات الخطاب الموسيقي في تونس اشكالية تحديد المفاهيم - قوجة, محمد (الحياة الثقافية, 2007)

مكانة المتحف في المجتمع - حملاوي, علي (آثار, 2007)
يشكل علم المتاحف مفترقا لمختلف مجالات العلوم الإجتماعية، تكون ضمن علم الإجتماع عندما يتعلق الامر بمكانة المتحف في المجتمع و ذلك من خلال تفحص نوعية الجماهير .

Geçmişten Günümüze Kuzey Afrika’da Mezhep Tartışmaları Ve Günümüze Yansımaları - Dalkiliç, Mehmet (ICANAS Uluslar arası Sempozyumu, 2007)

«أهل الله وخاصته»؛ المستظهرون لكتاب الله العزيز بالقرارة (الحياة, 2007)

إلى أستاذي الأديب؛ محمد بن قاسم ناصر بوحجام - أمبوعلي, يوسف بن أحمد (الحياة, 2007)

آثار النهضة العلمية التونسية في فكر الحركة الإصلاحية بوادي ميزاب - الشيخ بالحاج, قاسم بن أحمد (الحياة, 2007)
Keywords: Réformisme -- Mzab

إلى إخواني الطلبة - الشيخ بالحاج, محمد بن بكير (الحياة, 2007)

أفارس أم حمار؟ - الغماري, مصطفى محمد (الحياة, 2007)

العمانيون ونشر الإسلام والثقافة العربية في شرق إفريقيا - المعولي, زياد بن طالب (الحياة, 2007)

هل يضير نباح نجمَة سطعت؟ - باجو, صالح بن إبراهيم (الحياة, 2007)

المنهج الإسلامي في التوازن بين واجبات المسلم المعاق واحتياجاته الخاصة - باجو, مصطفى بن صالح (الحياة, 2007)

فجر الكرامة - باجو, مصطفى بن صالح (الحياة, 2007)

تعليمية النص القرآني في إطار التكوين الجامعي المتخصص في اللغة العربية وآدابها - بوتردين, يحيى بن صالح (الحياة, 2007)
Keywords: Coran -- apprentissage

الافتتاحية - بوحجام, محمد بن قاسم ناصر (الحياة, 2007)

كيف نتعامل مع التراث؟ - بوحجام, محمد بن قاسم ناصر (الحياة, 2007)

الحياة الثقافية بمنطقة أريغ، من القرن الرابع إلى السادس للهجرة - بوعصبانة, عمر بن حمو سليمان (الحياة, 2007)

التنشئة السياسية، أولوية حضارية ومستقبلية - حجاج, قاسم بن حمو (الحياة, 2007)

حياة من أجل القرآن..! - حدبون, صالح بن أحمد (الحياة, 2007)

فقه المال العام عند الإباضية (الحلقة الأولى) - حمدي, محمد بن صالح (الحياة, 2007)
Keywords: Fiqh

المجتمع المزابي ونسق القيم، من ضبطية التغير إلى تغير الضبط - خواجة, عبد العزيز بن محمد (الحياة, 2007)

بيداغوجيا التدريس والتقويم في العلوم الشرعية (مادة الفقه المقارن نموذجا) - دباغ, محمد (الحياة, 2007)
Keywords: Fiqh

كيف تلقي درسا وعظيا في العقيدة؟ (الخلود نموذجا) - شريفي, مصطفى بن محمد (الحياة, 2007)

خطبة العدد: خطبة عيد الفطر المبارك 1427هـ/2006م - كرشوش, يوسف بن سليمان (الحياة, 2007)

موقف سُكان وادي مزاب من التجنيد الإجباري في الجيش الفرنسي - ناصر, بالحاج بن باحمد (الحياة, 2007)
Keywords: Service militaire obligatoire‎ -- Mzab -- période coloniale

عميد التاريخ الوطني - ناصر, محمد صالح (الحياة, 2007)

كتاب «شرح أصول الدين» للشيخ اطفيش دراسة وتحقيق القسم الأول - وينتن, مصطفى بن الناصر (الحياة, 2007)
Keywords: Atfiyyash, Muhammad b. Yusuf (1821-1914)

كيف نعلم العقيدة في المدارس القرآنية؟ - وينتن, مصطفى بن الناصر (الحياة, 2007)

البعد الروحي لنظام حلقة العزابة - بوحجام, محمد بن قاسم ناصر (التسامح, 2007)

أبو اسحاق اطفيش في مصر - يطو, عائشة (مجلة معهد المخطوطات العربية, 2007)
Keywords: Aṭfiyyash, Ibrāhīm b. Muḥammad (1886-1965)

Omān mondai to imāmu-koku: Imāmu-koku no kōchiku to bōkyaku katei - Matsuo, Masaki (Utsunomiyadaigaku kokusai gakubu kenkyū ronshū, 2007)

Review of Oman: The Islamic Democratic Tradition - Solomon, Gina; Latorre, Aida (Middle East Studies Association Bulletin, 2007)
Keywords: Recension

Review of The Emergence of States in a Tribal Society: Oman under Sa'id bin Taymur, 1932-1970 - Allen, Jr, Calvin H. (Middle East Journal, 2007)
Keywords: Recension

الثوابت والمرتكزات في السياسة الخارجية العمانية - القطاطشة, محمد حمـد; الحضرمي, عمر حمدان (المنارة, 2007)
Keywords: Politique étrangère -- Oman -- 1970-2020

Parler berbère en famille : une revendication identitaire - Filhon, Alexandra (Revue européenne des migrations internationales, 2007)
Keywords: Linguistique -- Djerba

اتفاقية البريمي بين الدولة السعودية الثانية وسلطنة مسقط وعمان - العنقري, حمد بن عبد الله (الدارة, 2007)
تناقش هذه الدراسة العلاقات السعودية العمانية في القرن الثالث عشر الهجري/ ‏التاسع عشر الميلادي، وذلك من خلال اتفاقية البريمي المبرمة بينهما. وتسعى هذه ‏الدراسة إلى نشر نص الاتفاقية عن أصلها العربي لا سيما أن هذا الأصل لم يسبق أن ‏نشر من قبل.‏‎ ‎وتكمن أهمية هذه الاتفاقية من أنها اتفاقية سياسية تعود لعهد الدولة السعودية ‏الثانية، التي يندر أن يجد الباحث وثائق سياسية أو دبلوماسية لها، ناهيك عن ‏الدولة السعودية الأولى؛ نظرًا للأحداث التي حصلت في نهاية كل فترة منهما؛ إضافة ‏إلى قلة الوثائق العامة العائدة إلى تلك الفترة، ولعل من أسباب قلة الوثائق ‏المحلية اندثار الكثير منها بسبب تعاقب الزمن، وتعرض بعضها للحرق والتلف، ‏ورداءة الحبر والورق المستخدم، ولهذا تبرز أهمية ما يتوافر لدى الأراشيف العالمية ‏من وثائق محلية.‏‎ ‎
Keywords: Relations -- Oman -- Arabie Saoudite

Le problème des excédents hydriques à Ouargla : situation actuelle et perspectives d’amélioration - Idder, Tahar (Sécheresse, 2007)
Keywords: Irrigation -- Ouargla

On the Swahili Documents in Arabic Script from the Congo (19th Century) - Luffin, Xavier (Swahili Forum, 2007)
Si les documents rédigés en kiswahili à l’aide des caractères arabes provenant d’Afrique de l’Est sont bien renseignés depuis longtemps, qu’il s’agisse de correspondance ou de littérature, l’existence de tels documents provenant d’Afrique Centrale, et en particulier du Congo, est encore très mal connue. Pourtant, outre les témoignages de divers observateurs ou acteurs européens des débuts de la colonisation, plusieurs documents conservés pour la plupart en Belgique ont subsisté jusqu’à nos jours. Il s’agit essentiellement de la correspondance de marchands swahilis établis dans l’ancien district des Stanley Falls, mais aussi de traités, d’échanges «diplomatiques» ou de notes personnelles, remontant essentiellement aux deux dernières décennies du 19ème siècle. Ces documents se révèlent être une source intéressante à la fois pour l’Histoire du Congo précolonial et pour l’étude diachronique du kiswahili et de son expansion géographique.

Curing the Cancer of the Colony: Bagamoyo, Dar es Salaam, and Socioeconomic Struggle in German East Africa - Fabian, Steven (The International Journal of African Historical Studies, 2007)
Keywords: Esclavage -- Zanzibar

Review : Oman under Qaboos. From Coup to Constitution, 1970-1996 - Hertog, Stephen (British Journal of Middle Eastern Studies, 2007)
Keywords: Recension

Clove plantations on nineteenth-century Zanzibar: Possibilities for gender archaeology in Africa - Croucher, Sarah K. (Journal of Social Archaeology, 2007)
Clove plantations on nineteenth-century Zanzibar were sites on which many recent immigrants from Oman and Africa constructed new identities within the complex social relations of colonial rule, enslavement and concubinage. Archaeological evidence relating both to architectural and ceramic remains is used within this work to interpret such multifaceted identities. Ethnographic and historical accounts of African societies have both shown that gendered identities across the continent are, and have been in the past, characterized by diversity. This article has a wider signiﬁcance beyond the ﬁeld of African archaeology, in suggesting that archaeologists working across Africa are ideally placed to make an important contribution to the ﬁeld of gender archaeology in exploring such heterogeneous subjectivities.
Keywords: Zanzibar

Le Gisement Solaire à Ghardaïa - Benkaciali, S. (Bulletin des Energies Renouvelables, 2007)
Ce travail présente une étude qualitative et quantitative du trouble atmosphérique au site de Ghardaïa. Il s’agit de la détermination du facteur de trouble de Linke T*L, à partir des mesures instantanées données par une station radio métrique, qui utilise un système de poursuite à trois dimensions. Les mesures effectuées ont permis de déterminer ce coefficient, et de prédire sa variation annuelle et mensuelle qui présente un maximum au moi d’août (l’absorption par la vapeur d’eau est importante et une faible diffusion par les aérosols) et aussi une valeur importante du trouble au mois de juin (forte diffusion par les grains de sables), et un minimum en hiver (faible absorption par la vapeur d’eau et faible diffusion par les aérosols), à l’exception d’une période courte des tempêtes de sable (entre Mars et Mai) où la diffusion des aérosols grain de sable est prépondérante. D’après notre étude et nos observations sur site, on a constaté qu’il y a deux saisons principales à Ghardaïa (chevauchement des deux saisons).
Keywords: Energies renouvelables -- Mzab

Towards a new theory: the state of Banī Mahdī, the fourth imamate in Yemen - Zaylaʿī, Aḥmad b. ʿUmar al- (Proceedings of the Seminar for Arabian Studies, 2007)
Keywords: Archéologie -- Oman

Review: [Muslim Rebels: Kharijites and the Politics of Extremism in Egypt, by Jeffrey T. Kenney. New York: Oxford University Press, 2006. xi + 184 pages. Notes to p. 205. Bibl. to p. 216. Indexto p. 221. $45.] - Jankowski, James (Middle East Journal, 2007)
Keywords: Recension

Devout Heretics: The Barghawata in Maghribi Historiography - Iskander, John (The Journal of North African Studies, 2007)
From the mid-eighth century to at least the mid-twelfth century, a Berber people known as the Barghawata existed increasingly uncomfortably on the western fringes of North Africa. The medieval Arabic histories depict them in ways that show an increasing ambivalence towards their distinctive religious practices, eventually leading to utter condemnation. Yet these same histories preserve depictions that show that the Barghawata were not always thought of as heretics to be vanquished. The historiographic shift charted here is reﬂective of several dynamics. Some are broad, such as the increasingly uniform ideal of orthodoxy in the region; others are speciﬁc, such as the Marinids’ quest for a legitimising ideology, which led scholars to rethink aspects of the tribal past, as well as encouraging the rulers to support the growth of madrasas in Tunisia and beyond. The Barghawata’s image was increasingly reduced to a caricature, one that was subtly contradicted by the earlier sources.

Les itinéraires d’al-Idrīsī dans le Sud tunisien: deux versions bien différentes - Prevost, Virginie (Zeitschrift der Deutschen Morgenländischen Gesellschaft, 2007)

L’influence de l’État rustumide dans le Sud tunisien - Prevost, Virginie (Acta Orientalia, 2007)
Keywords: Dynastie rustumide

La Qasṭīliya médiévale et la toponomie du Djérid tunisien - Prevost, Virginie (Folia Orientalia, 2007)

Chronologie des événements en Oman en 2006 - Valeri, Marc (Chroniques yéménites, 2007)
Keywords: Vie politique -- Oman -- 1970-2020

Something Stirring under the Still Waters of Oman: Tightening the Grip or Revitalizing the Monarchy? - Valeri, Marc (Chroniques yéménites, 2007)
Keywords: Vie politique -- Oman -- 1970-2020

Entre foi et compromis tribal : L’entrée de la région d’Oman dans l’islam - Moez, Dridi (Chroniques yéménites, 2007)

Antīğān, un toponyme ibadite chez al-Idrisi - Prevost, Virginie (Al-Andalus Magreb, 2007)
In his short description of the western part of the island of Jerba, al-Idrīsī (in his K. Nuzhat al-Mushtāq fī Ikhtirāq al-Āfāq) mentions Antījān. This toponym is well known by the Ibāḍite historians since the first Jerban Ḥalqa was founded at this place at the end of the 11th century.
Keywords: Monuments -- Djerba; Tîwâjin, mosquée (Tîwâjin, Djerba)

The Emergence of States in a Tribal Society: Oman under Sa'id bin Taymur, 1932-1970by Uzi Rabi - Kechichian, Joseph Albert (The International History Review, 2007)
Keywords: Recension

رأي وهب بن منبه في الخوارج - الشويعر, محمد بن سعد (الداعي, 2007)
Keywords: Kharijisme

صورة المرأة في شعر الخوارج في العصر الأموي - دوابشة, محمد أحمد (مجلة جامعة النجاح للأبحاث, 2007)
يحاول هذا البحث رسم صورة للمرأة في شعر الخوارج في العصر الأموي، وإظهار نفسيتها وعواطفها تجاه ما يدور حولها من خلافات فكرية واجتماعية، فرضتها عليها طبيعة ذلك العصر، ويركز على إبراز موقفها تجاه الأحزاب المتصارعة، معتمدا على شعرها وشعر غيرها فيها، متبعا المنهج الوصفي التحليلي في دراسة الاشعار وتحليلها، كونها أقرب المناهج النقدية إلى ذلك العصر.
Keywords: Poésie kharijite

جذور الأباضية في بلاد المغرب - عياش, عدنان حسين (مجلة اتحاد الجامعات العربية للآداب, 2007)
ارتبط ظهور الخوارج في بلاد المغرب بالتطور السياسي الذي حدث لهم في المشرق الإسلامي في أواخر القرن الأول الهجري، فبعد فشل ثوراتهم في قلب العالم الإسلامي اتبعوا أسلوب الدعوة والتنظيم السياسي في الأمصار الإسلامية القاصية ووجد الخوارج في بلاد المغرب ميداناً خصباً لنشر مذهبهم، وفي الحقيقة أن الخوارج وخاصة الإباضية منها قد قفزت إلى بلاد المغرب في أعقاب الفتح الإسلامي لبلاد المغرب رغبة منهم في الحصول على ميدان جديد ينشرون فيه تعاليمهم المناهضة لنظام الحكم الأموي والعباسي من بعده وتتقدم الإباضية بين البربر وتلقى نجاحا ًكبيراً بينهم وذلك بسبب سوء معاملة بعض الولاة الأمويين والعباسيين من بعدهم للبربر خاصة في بلاد المغرب. وعلى هذا الأساس يمكن القول بان جمهور الخوارج الإباضية هي المقدمات الحقيقية للبناء السياسي لبلاد المغرب لان هؤلاء الإباضية في سنة 160ه/777م تمكنوا من الانتقال من مرحلة الدعوة إلى مذهبهم إلى مرحلة التطبيق العملي لمبادئهم.

مسقط : حاضرة الساحل والمحيط - Wilkinson, John Craven (التفاهم, 2007)

Un siècle de pharmaciens du Sud Tunisien - Besbes, Rachid (Essaydali de Tunisie, 2007)
Keywords: Médecine -- Djerba

Oman: A Thousand Years of Democratic Tradition * by Hussain Ghubash - Jones, Jeremy (Journal of Islamic Studies, 2007)
Keywords: Recension

Teachers, Scholars and Educationists: The Impact of Hadrami-'Alawi Teachers and Teachings on Islamic Education in Zanzibar ca. 1870–1930 - Bang, Anne K. (Asian Journal of Social Science, 2007)
Hadrami scholars have long been recognized as well as been influential teachers of East African Islam, especially in the late 18th and early 19th century. is article traces the role of Hadrami teachers and scholars on Islamic education in Zanzibar between c. 1870 and 1930. The article analyses different levels of Islamic education and traces the texts and teachers who came to influence generations of Muslims in the British-Bū Saīdī protectorate.
Keywords: Zanzibar

Efficacité comparée de trois méthodes de lutte contre la Cochenille blanche du Palmier-dattier dans la région de Ouargla (Sud-est algérien) (Hemiptera, Diaspididae) - Idder, Mohamed Azzedine; Bensaci, Mohamed; Oualan, Mohamed; Pintureau, Bernard (Bulletin de la Société entomologique de France, 2007)
Trois méthodes de lutte ont été appliquées contre la Cochenille blanche du Palmier-dattier Parlatorio blanchardi (Targioni-Tozzetti) en Algérie. La lutte physique à l'aide du flambage a conduit à un pourcentage de mortalité des cochenilles de 92,2 et semble être la plus efficace. La lutte chimique à l'aide d'un insecticide a eu un effet significatif puisqu'elle a provoqué des pourcentages de mortalité de 73,2 et 80,0 selon la parcelle. La lutte biologique à l'aide de Coccinelles a quant à elle conduit à des pourcentages de mortalité relativement faibles, de 18,1 et 19,7. Il faut toutefois aussi tenir compte de l'effet de la méthode de lutte sur les populations d'auxiliaires avant d'opter pour l'une d'entre elles. Or, nous avons constaté que les traitements physique et chimique ont provoqué une très forte mortalité des auxiliaires (78,8 à 89,4%). En revanche, la méthode biologique a préservé la faune utile et donc l'équilibre biologique dans le biotope. Cette dernière méthode semble ainsi mieux adaptée au milieu palmeraie, agro-système à la fois complexe et fragile où toute perturbation brutale peut être fatale et irréversible.
Keywords: Botanique -- Ouargla

Une découverte de "guerriers libyens" au Mzab et des conséquences pour l'historiographie du Maghreb - Hachid, Malika (Les Cahiers de l'AARS, 2007)
Keywords: Antiquité

Abitazioni rupestri a Nalut (Libia). Seconda missione, febbraio 2007. - Dell'Aquila, Franco; Bencini, Claudio; Fiorentino, Giuseppe (Grotte e dintorni, 2007)
Nel presente lavoro sono state descritte e analizzate per la prima volta diverse abitazioni rupestri nel Gebel Nefusa libico. Sono stati studiati anche alcuni villaggi rupestri e gasr edificati con pietra e malta di gesso, prodotti nella regione. Per
Keywords: Architecture -- Djebel Nefousa

Libia sconosciuta: Nalut ed il Jebel Nafusah: le abitazioni rupestri dei Berberi, i depositi di cereali, i granai fortificati, i frantoii e le tecniche di coltivazione secca - Bencini, Claudio; Dell'Aquila, Franco (L'Universo, 2007)
Keywords: Architecture -- Djebel Nefousa

The Ghirian tertiary volcanic province of Tripolitania, Libya - Almond, D. C.; Busrewil, M. T.; Wadsworth, W. J. (Geological Journal, 2007)
Keywords: Géologie -- Djebel Nefousa

Production et commercialisation des vanneries dans les oasis du Sahara - Benfoughal, Tatiana (Journal des africanistes, 2007)
Le tressage des vanneries fait partie des activités des cultivateurs des oasis, parce qu’ils ont à leur disposition la matière première tirée du palmier dattier qui permet de produire un nombre considérable d’objets indispensables au travail agricole et à la vie quotidienne. Dans la pratique oasienne, il y a plusieurs modes de fonctionnement, depuis la production domestique jusqu'à l’artisanat, en passant par différentes formules transitoires. Les transformations actuelles des sociétés sahariennes bousculent les fonctionnements traditionnels et complexifient les modes socio-économiques de cette activité.

Salt tolerance of the annual halophyte Cakile maritima as affected by the provenance and the developmental stage - Megdiche, Wided; Ben Amor, Nader; Debez, Ahmed; Hessini, Kamel; Ksouri, Riadh; Zuily-Fodil, Yasmine; Abdelly, Chedly (Acta Physiologiae Plantarum, 2007)
Though halophytes are naturally adapted to salinity, their salt-tolerance limits are greatly influenced by their provenance and developmental stage. In the present study, physio-biochemical responses of two Tunisian ecotypes of the oilseed coastal halophyte Cakile maritima (Brassicaceae) to salinity (0–400 mM NaCl) were monitored during germination and vegetative growth stages. Tabarka and Jerba seeds were collected from humid or arid climatic areas, respectively. Plant response to salinity appeared to depend on the ecotype and salinity levels. Increasing salinity inhibited germination process. Jerba seeds were found to be more salt tolerant than the Tabarka ones. At the autotrophic stage of growth and under salt-free conditions, Jerba was less productive than Tabarka (in terms of dry matter accumulation), but plant biomass production and leaf expansion (area and number) of the former ecotype were progressively improved by 100 mM NaCl, as compared to the control. In contrast, at the same salt concentration, these parameters decreased under increasing salinity in Tabarka (salt sensitive). Leaf chlorophyll content was reduced at severe salinity, but this effect was more conspicuous in the sensitive Tabarka plants. Na+ contents in the Jerba and Tabarka leaves collected from the 400 mM NaCl-treated plants were 17- and 12-fold higher than in the respective controls. This effect was accompanied by a significant reduction in the leaf K+, Mg2+ and Ca2+ contents, especially in the salt-treated Tabarka. A significant accumulation of proline and soluble carbohydrates in leaves was found during the period of intensive leaf growth. These organic compounds likely play a role in leaf osmotic adjustment and in protection of membrane stability at severe salinity.
Keywords: Botanique -- Djerba

Les dernières communautés chrétiennes autochtones d’Afrique du Nord - Prevost, Virginie (Revue de l’histoire des religions, 2007)
Keywords: Christianisme -- Djebel Nefousa

La pourpre de « Meninx » - Drine, Ali (Africa : Revue des Études et Recherches préhistoriques, antiques, islamiques et ethnographiques, 2007)
Keywords: Archéologie -- Djerba

A Fifth Century BCE Graffito from Ghizène (Jerba) - Schmitz, Philip; Docter, Roald F.; Ben Tahar, Sami (Orientalia, 2007)
Keywords: Antiquité; Archéologie -- Djerba

Les entrepôts de Méninx - Drine, Ali (Antiquités africaines, 2007)
Keywords: Antiquité; Archéologie -- Djerba